(3PcQ eG jJab ef CSeGA GdeMOKjf hCfSGHges - (3GdNWjH GdHZOGOj , CMeO Hf Ydj Hf KGHJ , CHh HcQ , J (B463 (3g` s ((3CMeO Hf CHj eMeO Hf CHj GdbGSe GdfLGQ GdebQi s)
(3ChdgG (B:s
(3HYO GdOjHGLg (B: (3hdeG GfJgi aQGZi ef cJGH GdJdNjU GJHYJg HPcQ eG jJab ef CSeGA GdeMOKjf hCfSGHge s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B172 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B3s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B152 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs